(3eMGVQGJ aj ebGjjS eONd ddEbJUGO, eONd dEOGQI GdCYeGd, JGQjN GdhbGFY GdEbJUGOjI, JcfhdhLjG GdeYdheGJ aj GdeDSSI, EOGQI GdeYQaIs - (3eYjf Cejf(B, (3GdSjOs ((3GdLRGFQ(B:s (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQ(B,s, 2018)
(3JfGhd gPG GdcJGH eMGVQGJ aj ebGjjS GdJGdjI(B: (3eONd ddEbJUGO h eONd dEOGQI GdCYeGd hJGQjN GdhbGFY GdEbJUGOjI , hJcfhdhLjG GdeYdheGJ aj GdeDSSI hEOGQI GdeYQaIs
Keywords: (3EOGQI GdCYeGds; (3EOGQI GdeYQaIs; (3GdEbJUGOs; (3GdhbGFY GdGbJUGOjI (B- (3JGQjNs